Analisis Hubungan Pendapatan Bukan Pertanian, Kemiskinan dan Ketaksamarataan Pendapatan Dalam Kalangan Petani: Kajian Kes di Kedah Darul Aman - Siti Hadijah, Che Mat (2010)
This study is motivated by the observation that poverty and inequality in the agricultural-rural areas in Malaysia had been declining significantly. The question that arises then, what is the underlying explanations for this declining trend in poverty and inequality? Official government documents usually report aggregate index of poverty and inequality. This aggregate measure of poverty and inequality therefore is obtained from total household income, i.e. as if, it is derived from a single source of income. However, agricultural household income is usually derived from various sources - farm and non-farm income sources. Indeed, past studies found that the percentage of non-farm income sources in total agricultural household income has been increasing in developing countries. Thus, it is possible that one of these sources is accountable for the decline in poverty and inequality among the agriculturai-rural households. The main argument advanced in this study is that one of the possible key explanations for the decline in poverty and inequality observed among the agricultural-rural households in Malaysia is probably due to the impact of non-farm income sources. Participation of farmers in non-farm activities will increase their total income and hence, reduce poverty. It is postulated that it is the lower income group among the farmers that will have higher probability to participate in non-farm activities, since they are the one who need additional income for their living. If this is the case, then this might expiain why income inequality among the agricultural-rural household is declining. It appears that investigation on this issue escape past studies on poverty and inequality in Malaysia. The objectives of this study are therefore to: (i) analyze the determinants of farmer's participation in non-farm activities; (ii) analyze the impact of non-farm income sources on poverty and (iii) analyze the impact of non-farm income sources on inequality. This study used primary data, collected among agricultural households in Kedah Darul Aman. Respondents are chosen based on two stage stratified random sampling and quota. First, six out of the eleven districts in Kedah are chosen. The number of respondent for each district chosen is to be proportionate to the total number of farmers in the district. Second, within each district the respondents are chosen based on their local economic characteristics. There are four local economic characteristics - agriculture and industrial area, mainly agriculture area, neither agriculture nor industrial area, and mainly industrial area. This is to enable investigation to be carried out on the impact of local economic characteristics on the likelihood of farmer's participation in non-farm activities. With regards to the first objective, this study employs logit model to estimate the determinants that will have an impact on the likelihood of farmers to participate in non-farm activities. For the second objective, this study employs poverty decomposition method. Specifically, this study decompose Foster, Greer dan Thorbecke index (FGT index) as carried out by Adams (2004). The FGT decomposition analysis enables the FGT index to be separated to its various income sources contribution (farm and non-farm sources) to total poverty. Finally, to achieve the third objective, this study carried out inequality decomposition exercises to investigate the impact of non-farm income sources on inequality. The decomposition of the Gini coefficient is also carried out following Lerman and Yitzhaki (1985) and Stark, Taylor and Yitzhaki (1986). Following their methods it is possible to determine whether non-farm income is an equalising or a disequalising factor. The findings of this study show that non-farm income sources contributed about one-third of the total agricultural household income. Besides, decomposition exercises carried out on poverty index shows that non-farm income sources contributed significantly towards poverty reduction among agricultural households. With regards to farmers' participation in non-farm activities, this study discovers that age, gender, household size, number of dependent, remittance, land size, and type of agricultural activities are the main determinants. It is also worth highlighted that local economic characteristics(structure), a variable that appears to be overlooked in past studies, is also found to be highly significant. Furthermore, decomposition of the Gini coeficient uncovers that non-farm income sources is an income dis-equalising factor. Thus, analysis in this study found that while non-farm income sources contributed towards poverty reduction among agricultural households, it is also an income dis-equalising factor among the agricultural households. The policy implication of this study is that, non-farm income activities should be encouraged among agricultural households as this would raise their income and hence, reduce poverty among them. However, it should be focused on value-added activities, especially on the lower income group. The findings of this study also suggest that a balanced development approach should not only focus on rural-urban divide, but also within the rural areas itself.